Un bisogno di complementarità Il carteggio Cassola-Fortini - Perciballi, Giada (Carteggi e materiali del Centro Interdipartimentale di ricerca Franco Fortini, 2023)
The correspondence between Franco Fortini and Carlo Cassola covers a wide range of time, from 1955 to 1981 and focuses on three core themes: the journey to China in 1955 and the writing of two reportages on this topic; the events of 1965 and the literary fervour arisen around left-wing journals; Cassola's poetic and literary production, enriched with Fortini's critical notes. However, and the same time, the correspondence between Cassola and Fortini also shows the birth (and developments) of a complex relationship, characterized by friendship and reciprocal influence, that involves two among the most well-known figures of the twentieth century. The correspondence represents a unique resource for the analysis of the legacy, poetics and cultural background of the two great authors.